Knowledge, Attitudes and Practices in Antibiotic Use in Family Medicine Students - Xavier Sánchez; Andrea Landázuri; Paulina Londo; Andrea Manzano; Andrés Moreno Roca; Ruth Jimbo (SAGE Publishing, 2020)
Background Inappropriate prescriptions of antibiotics lead to ineffective and unsafe treatments and worsening of diseases. Medical students may have deficiencies in their prescription skills and they may need further training in the use of antibiotics for their practice. Medical skills in prescribing antibiotics can be improved through continuous medical education. The aim of this study was to assess the current levels of knowledge, attitudes, and practices (KAP) in antibiotic prescription in upper respiratory tract infections (URTI) among postgraduate family medicine students in Ecuador. Methods A cross-sectional study with an on-line survey, based on micro-curricular contents, to evaluate KAPs regarding antibiotic prescription in URTI among postgraduate family medicine students in 5 provinces of Ecuador. Results Two hundred and seventy-three physicians responded (94.1%). Most physicians treated between 1 and 5 URTI cases per day. The odds for inadequate knowledge and inappropriate practices in URTI among postgraduate family medicine students were 8.74 (95%CI, 4.94-15.46, P  < .001) and 5.99, (IC95%, 2.66-13.50, P  < .001) in physicians who were students of the first half of the study program. Conclusion The knowledge in URTI was limited among physicians. Nonetheless, they expressed a positive attitude toward not using antibiotics in URTI. A postgraduate program can significantly improve the knowledge and practices related to antibiotic prescriptions in URTI.